Prairie man : my Little House life & beyond - Butler, Dean, 1956- (Citidel Press, Kensington Publishing Corp., 2024)
An illuminating, insider's journey through the world of Little House on the Prairie and beyond, from Dean Butler, who starred as Almanzo Wilder, the man Laura "Half Pint" Ingalls married--on the iconic show still beloved by millions of fans as it reaches its 50th anniversary.